2022
DOI: 10.3897/mbmg.6.85213
|View full text |Cite
|
Sign up to set email alerts
|

The potential of metabarcoding plant components of Malaise trap samples to enhance knowledge of plant-insect interactions

Abstract: The worldwide rapid declines in insect and plant abundance and diversity that have occurred in the past decades have gained public attention and demand for political actions to counteract these declines are growing. Rapid large-scale biomonitoring can aid in observing these changes and provide information for decisions for land management and species protection. Malaise traps have long been used for insect sampling and when insects are captured in these traps, they carry traces of plants they have visited on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 581 publications
(14 citation statements)
references
References 51 publications
0
14
0
Order By: Relevance
“…Within the framework of DINA, we were able to demonstrate that Malaise trap samples can be used not only for studies on insect species richness and biomass, but also to examine traces carried into the traps by insects to analyse plant species richness through metabarcoding (Swenson et al 2022) and pesticide residues in ethanol (Brühl et al 2021). Results from our Malaise trap transect studies for the analysed sampling intervals show a clear positive correlation between insect species richness and insect biomass, confirming previous observations in Europe among certain insect taxa such as hoverflies (Diptera: Syrphidae; Hallmann et al 2021a).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Within the framework of DINA, we were able to demonstrate that Malaise trap samples can be used not only for studies on insect species richness and biomass, but also to examine traces carried into the traps by insects to analyse plant species richness through metabarcoding (Swenson et al 2022) and pesticide residues in ethanol (Brühl et al 2021). Results from our Malaise trap transect studies for the analysed sampling intervals show a clear positive correlation between insect species richness and insect biomass, confirming previous observations in Europe among certain insect taxa such as hoverflies (Diptera: Syrphidae; Hallmann et al 2021a).…”
Section: Discussionmentioning
confidence: 99%
“…Sequencing data were processed with USEARCH (Edgar 2010) and DADA2 (Callahan et al 2016) using R (R Core Team 2019). The resulting ASVs were identified by implementing the SINTAX algorithm (Edgar 2016) using a custom Plantae reference database (Swenson et al 2022) (for full outline see Online Resource 2, Plant metabarcoding).…”
Section: Plant Metabarcodingmentioning
confidence: 99%
See 1 more Smart Citation
“…The DINA project (Diversity of Insects in Nature protected Areas), a comprehensive interdisciplinary research project involving eight institutions (Lehmann et al, 2021), investigates the influence on insect populations in nature reserves as part of SAC and within the European Natura 2000 network (Brühl et al, 2021; Eichler et al, 2022; Köthe et al, 2023a; Lehmann et al, 2021; Swenson et al, 2022). Based on the original model to study the main drivers for the decline in insect biomass (Hallmann et al 2017), we focused on the already identified covariates: the influence of arable land and the chemical inputs such as nitrogen and pesticides associated with intensive land use.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, due to the comparability in methodology, the data can be collated with those of Hallmann et al (2017). In addition to insect data, landscape elements and their spatial distribution pattern (Eichler et al, 2022), vegetation (Köthe et al, 2023b; Swenson et al, 2022), and pesticide residues were measured (Brühl et al, 2021) accompanied by exchange with local stakeholders for developing solutions for improved insect protection (Fickel et al, 2020; Köthe et al, 2023a; Lehmann et al, 2021).…”
Section: Introductionmentioning
confidence: 99%